2022
DOI: 10.3390/mi13091372
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride Nanoribbons Grown by Chemical Vapor Deposition for VUV Applications

Abstract: The fabrication process of vacuum ultraviolet (VUV) detectors based on traditional semiconductor materials is complex and costly. The new generation of wide-bandgap semiconductor materials greatly reduce the fabrication cost of the entire VUV detector. We use the chemical vapor deposition (CVD) method to grow boron nitride nanoribbons (BNNRs) for VUV detectors. Morphological and compositional characterization of the BNNRs was tested. VUV detector based on BNNRs exhibits strong response to VUV light with wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…and Ort-B 16 N 16 , which can be considered three-dimensional structures assembled from B 16 N 16 cage clusters. Based on the density functional theory modified by Van der Waals, the following interesting features of Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 were characterized: (i) they were low-density (2.124 g/cm 3 , 2.379 g/cm 3 , and 2.163 g/cm 3 , respectively) porous materials, due to the existence of boron nitride hollow cages B 16 N 16 ; (ii) Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 exhibited good energy and dynamic, thermal, mechanical, and chemical stability, due to the strong covalence interaction between B and N atoms, which was proven by our electron localization function analysis; (iii) the results of elastic properties calculations showed that Cub-B 16 N 16 and Tet-B 16 N 16 were brittle materials, but Ort-B 16 N 16 was ductile; the Young's moduli and shear moduli of the three assembled materials harbored strong anisotropy; (iv) the electronic band structure showed that the three assembled crystal phases were all indirect wide-band gap semiconductors. Our results not only highlighted some novel low-density boron nitride polymorphs, they also provided a bottom-up way to design new solid materials by using the clusters as building blocks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…and Ort-B 16 N 16 , which can be considered three-dimensional structures assembled from B 16 N 16 cage clusters. Based on the density functional theory modified by Van der Waals, the following interesting features of Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 were characterized: (i) they were low-density (2.124 g/cm 3 , 2.379 g/cm 3 , and 2.163 g/cm 3 , respectively) porous materials, due to the existence of boron nitride hollow cages B 16 N 16 ; (ii) Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 exhibited good energy and dynamic, thermal, mechanical, and chemical stability, due to the strong covalence interaction between B and N atoms, which was proven by our electron localization function analysis; (iii) the results of elastic properties calculations showed that Cub-B 16 N 16 and Tet-B 16 N 16 were brittle materials, but Ort-B 16 N 16 was ductile; the Young's moduli and shear moduli of the three assembled materials harbored strong anisotropy; (iv) the electronic band structure showed that the three assembled crystal phases were all indirect wide-band gap semiconductors. Our results not only highlighted some novel low-density boron nitride polymorphs, they also provided a bottom-up way to design new solid materials by using the clusters as building blocks.…”
Section: Discussionmentioning
confidence: 99%
“…For Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 structures, the average bond lengths were 1.519 Å, 1.530 Å, and 1.544 Å, respectively; the average bond angles of the four-membered rings were 93.6 • , 89.8 • , and 90.0 • ; and the six-membered rings were 119.2 • , 117.1 • , and 112.8 • , respectively. One can see that the mass densities of Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 were 2.124 g/cm 3 , 2.379 g/cm 3 , and 2.163 g/cm 3 , respectively, which were much lower than that of c-BN (3.472 g/cm 3 ) [34], Hp-BN (3.633 g/cm 3 ) [35], and Pm3n-BN (2.849 g/cm 3 ) [22], due to the existence of hollow holes. The optimized, nonequivalent atomic coordinates of Cub-B 16 N 16 , Tet-B 16 N 16 , and Ort-B 16 N 16 structures are shown in Table S1.…”
Section: Structural Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, based on the expectation of their excellent properties, researchers have gradually become interested in boron nitride nanomaterials with different morphologies. Nowadays, various types of BN nanostructures, such as BN nanoparticles [ 47 , 48 , 49 ], BN nanosheets [ 50 , 51 , 52 ], BN nanocapsules [ 53 ], BN nanoropes [ 54 ], BN nanoribbons [ 55 ], BN aerogels [ 56 , 57 ], BN single domains [ 58 ], BN films [ 59 ] and hexagonal boron nitride-based heterostructures [ 60 ], have attracted worldwide interest, not only for their fundamental scientific interest, but also for their unique properties and potential applications. Besides the BN nanostructures mentioned above, a new type of boron nitride structure with nanoflakes, whiskers, burrs or filaments growing on the surface of nanotubes was also reported, which has been named according to its different groups as a thorn-like BN nanostructure [ 61 ], collapsed BN nanotubes [ 62 ], surface-modified BN nanotubes [ 63 , 64 ], nanotubes decorated with BN nanosheets [ 65 ], a coral-like BN nanostructure [ 66 ], a BN micro-/nanostructure [ 67 ], a boron nitride hierarchical structure [ 68 , 69 ] or a boron nitride nanosheets–nanotubes hybrid structure [ 70 ].…”
Section: Introductionmentioning
confidence: 99%